Fatty Acid Supplementation During in vitro Embryo Production Determines Cryosurvival Characteristics of Bovine Blastocysts - Aardema, H.; Bertijn, I.; van Tol, HTA.; Rijneveld, A.; Vernooij, JCM.; Gadella, B. M.; Vos, PLAM (Frontiers in Cell and Developmental Biology, 2022)
In vitro production (IVP) embryos have a reduced quality and poor cryotolerance in comparison to in vivo embryos. This study investigated whether free fatty acid (FFA) conditions, fatty acid free (FAF)- synthetic oviductal fluid (SOF) without or with 25 μM of saturated stearic (C18:0) or unsaturated oleic (C18:1) acid during the first 5 IVP days, relate to quality and cryosurvival of day 8 blastocysts. Apart from the blastocyst scores, both 1) number and size of lipid droplets of fresh blastocysts and 2) total number and apoptotic and necrotic cells, before and after freezing-thawing, were scored by confocal microscopy. Blastocyst rates were significantly lower in the FAF SOF condition in comparison to other groups. Interestingly, blastocysts originating from the C18:1 group, with a significantly higher lipid content, and blastocysts from the FAF SOF group demonstrated a high cryosurvival rate (70.1% and 67.4%, respectively) comparable with in vivo blastocysts (68%), in contrast to the poor cryosurvival of C18:0 exposed embryos (17.6%). In all freeze-thawed embryos the average amount of apoptotic and necrotic cells increased albeit that the C18:0 condition rates were higher (43.2%) when compared to C18:1 (26.0%) and FAF SOF conditions (26.5%). The current data show that FFA administered during early embryonic development significantly affect the cryotolerance of blastocysts.